2010
DOI: 10.1063/1.3406149
|View full text |Cite
|
Sign up to set email alerts
|

In situ visualization of crystallization inside high temperature silicate melts

Abstract: The present work is concerned with the real time in situ visualization of crystallization processes inside strongly supercooled silicate melts using optical projection technique. The crystallization experiments are carried out for forsterite composition under container-less conditions. Starting material is heated above its liquidus temperature (2169 K) using a high power CO2 laser and crystallization is initiated following rapid cooling. Three different values of supercooling (ΔT≈320, 400, and 500 K, calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This assumption originates from the results of classical furnace-based crystallization experiments (e.g., ; however, several estimations based on some chondrule features, such as overgrowth thicknesses on relict grains (e.g., Wasson & Rubin 2003) and rim formation for barred olivine chondrules (Miura et al 2010b), give much higher cooling rates (∼ 200-2000 K s −1 ; Miura & Yamamoto 2014). Moreover, porphyritic textures may be reproduced by multiple melting processes (e.g., Rubin 2010) and they can also be formed via supercooled precursors (e.g., Srivastava et al 2010;Seto et al 2017). Therefore, dust enrichment is not necessarily needed for volatile retainment when the heating/cooling rates around their liquidus temperature are high enough.…”
Section: Volatile Retentionmentioning
confidence: 99%
“…This assumption originates from the results of classical furnace-based crystallization experiments (e.g., ; however, several estimations based on some chondrule features, such as overgrowth thicknesses on relict grains (e.g., Wasson & Rubin 2003) and rim formation for barred olivine chondrules (Miura et al 2010b), give much higher cooling rates (∼ 200-2000 K s −1 ; Miura & Yamamoto 2014). Moreover, porphyritic textures may be reproduced by multiple melting processes (e.g., Rubin 2010) and they can also be formed via supercooled precursors (e.g., Srivastava et al 2010;Seto et al 2017). Therefore, dust enrichment is not necessarily needed for volatile retainment when the heating/cooling rates around their liquidus temperature are high enough.…”
Section: Volatile Retentionmentioning
confidence: 99%
“…We carry out numerical simulations for a wide range of supercooling and cooling rate by using the phase-field method, which is one of the most effective numerical methods to simulate crystal growth in a supercooled liquid. As a first step, we consider the situation of container-less crystallization experiments using levitation methods (Tsukamoto et al, 1999(Tsukamoto et al, , 2001Nagashima et al, 2006Nagashima et al, , 2008Srivastava et al, 2010) because in these experiments the thermal profile of the droplet and the crystal growth pattern were observed in-situ, so we can verify the results of our numerical simulations. For comparison, we consider a droplet of pure forsteritic (Mg 2 SiO 4 ) composition, which was adopted in these experiments.…”
Section: Introductionmentioning
confidence: 87%
“…If T n / T hyp is smaller than 1, a remelting occurs. Accoring to the free-floating-crystallization experiment of a forsterite liquid by Srivastava et al (2010), a porphyritic texture was obtained with the value ∼0.7. Thus, a porphyritic chondrule could remelt momentarily by recalescence.…”
Section: Relict Grains In Porphyritic Chondrulesmentioning
confidence: 93%
“…Free-floating, laser-heating experiments using drop towers, high-speed gas flows or ultrasonic sound waves that levitate molten silicate charges remove the problem of preexisting solid nuclei (Nelson et al 1972;Blander et al 1976;Nagashima et al 2008;Srivastava et al 2010). These experiments have clearly shown that the supercooling degree of a melt charge is a crucial factor that determines petrographic textures upon its solidification.…”
Section: Petrographic Textures Of Chondrulesmentioning
confidence: 99%